THE EFFECT OF APPLICATION OF 5E LEARNING CYCLE MODEL COMBINED NUMBERED HEAD TOGETHER (NHT) TOWARD CHEMISTRY LEARNING OUTCOMES ON THE SUBJECT OF SALT HYDROLYSIS IN XI SCIENCE STUDENTS AT SENIOR HIGH SCHOOL 1 TANAH GROGOT ACADEMIC YEAR 2014/2015 - Yuni Kurnia; Usman -; Ratna Kusumawardani (PROSIDING SEMINAR KIMIA, 2015)
This study aims to determine the effect of application of 5E learning cycle modelcombined numbered head together (NHT) toward chemistry learning outcomes on the subject of salt hydrolysis in XI science students at Senior High School 1 Tanah Grogot academic year 2014/2015. The method is used in this study is experimental method. Samples were students of class XI Science 4 as an experimental class-treated with 5E learning cycle model combined numbered head together (NHT) and the students of class XI Science 3 as control class treated with direct instructional models. Obtaining the average value of 84,4 post-test experimental class and control class 73,8. Data analysis process two groups using t-test results obtained 3,24 ttest and ttable at 5% significance level of 1,67, then tcalculation> ttable. The results of this study indicate that there are. The effect of the 5E learning cycle modelcombined numbered head together (NHT) toward chemistry learning outcomes on the subject of salt hydrolysis in XI sains students at Senior High School 1 Tanah Grogot academic year 2014/2015.